2017
DOI: 10.1002/bies.201700077
|View full text |Cite
|
Sign up to set email alerts
|

Precarious maintenance of simple DNA repeats in eukaryotes

Abstract: In this review, we discuss how two evolutionarily conserved pathways at the interface of DNA replication and repair, template switching and break-induced replication, lead to the deleterious large-scale expansion of trinucleotide DNA repeats that cause numerous hereditary diseases. We highlight that these pathways, which originated in prokaryotes, may be subsequently hijacked to maintain long DNA microsatellites in eukaryotes. We suggest that the negative mutagenic outcomes of these pathways, exemplified by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 124 publications
1
37
0
Order By: Relevance
“…tract) (Usdin et al 2015;Neil et al 2017;Polleys et al 2017;Polyzos and McMurray 2017). We and others have also shown that trinucleotide repeat can induce mutagenesis at a distance (RIM-repeat induced mutagenesis) and trigger CGRs (Shah et al 2012;Saini et al 2013;Tang et al 2013).…”
mentioning
confidence: 85%
“…tract) (Usdin et al 2015;Neil et al 2017;Polleys et al 2017;Polyzos and McMurray 2017). We and others have also shown that trinucleotide repeat can induce mutagenesis at a distance (RIM-repeat induced mutagenesis) and trigger CGRs (Shah et al 2012;Saini et al 2013;Tang et al 2013).…”
mentioning
confidence: 85%
“…Recent literature has suggested that DSB may be responsible for large scale expansion in nondividing cells providing a potential mechanism for modification of repeat length and phenotypic variability [90,91]. DSB repair have two major repair pathways: homologous recombination repair (HRR) and nonhomologous end joining (NHEJ) [92].…”
Section: Double-strand Dna Repairmentioning
confidence: 99%
“…While mature postmitotic neurones in G0/G1 rely upon error prone NHEJ, break-induced replication (BIR) of homologous recombination can cause large-scale expansion in a CAG tract repeat cellular model in vitro [31,91]. Importantly, BIR may also occur in nondividing neurons and drive disease progression [91]. BIR is then initiated when a one-ended DSB undergoes 5 0 strand resection followed by invasion into a homologous sequence.…”
Section: Double-strand Dna Repairmentioning
confidence: 99%
See 2 more Smart Citations